The impact of electronic tax obligations on the formalization of micro and small peruvian companies - Tuesta Bardalez, Segundo Eloy (2020)
This article analyzes the impact of the electronic tax on the formalization of Peruvian micro and small enterprises (MYPE) in a cross-sectional period, from 2008 to 2017, based on the analytical-synthetic method and techniques of documentary review, descriptive Statistics and linear regression analysis, the primary information published by different public entities of the Peruvian State that interact in the economic sphere and business management. The results show that the successive regulatory reforms and tax management exercised by the tax administration (SUNAT) have not yet achieved a positive impact with the implementation and use of information and communication technologies in electronic tax, an impact that is evident in a low tax system pressure and a high risk tax base structure. The regression analysis of the tax base variable and collection of corporate income tax, shows a weak correlation, being unpredictable and corroborating that the business collection of the Peruvian tax system has a risky dependence of 0.6% of taxpayers denominated PRICOS. It also identifies important gaps in tax informality in Peruvian MYPE.